2015
DOI: 10.1124/dmd.115.066027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug Clearance and Drug-Drug Interactions in Microscale Cultures of Human Hepatocytes

Abstract: Accurate prediction of in vivo hepatic drug clearance using in vitro assays is important to properly estimate clinical dosing regimens. Clearance of low-turnover compounds is especially difficult to predict using short-lived suspensions of unpooled primary human hepatocytes (PHHs) and functionally declining PHH monolayers. Micropatterned cocultures (MPCCs) of PHHs and 3T3-J2 fibroblasts have been shown previously to display major liver functions for several weeks in vitro. In this study, we first characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 32 publications
2
79
0
Order By: Relevance
“…Our assays were done in primary human hepatocytes, and not tissues, treated with 2.5 mM metformin in order to observe significant metformin response, which is higher than physiological conditions used to treat metformin in patients. Our cells also do not mimic as well hepatocytes in their in vivo environment compared to more complex culturing conditions such as micropatterned cocultures [62] or a collagen sandwich system [63]. Due to the large costs and limited hepatocyte material, the cells were only treated in a single concentration of compound C (40 μM) which was previously shown to be effective in suppressing metformin-stimulated AMPK phosphorylation and glucose production [11,64].…”
Section: Discussionmentioning
confidence: 99%
“…Our assays were done in primary human hepatocytes, and not tissues, treated with 2.5 mM metformin in order to observe significant metformin response, which is higher than physiological conditions used to treat metformin in patients. Our cells also do not mimic as well hepatocytes in their in vivo environment compared to more complex culturing conditions such as micropatterned cocultures [62] or a collagen sandwich system [63]. Due to the large costs and limited hepatocyte material, the cells were only treated in a single concentration of compound C (40 μM) which was previously shown to be effective in suppressing metformin-stimulated AMPK phosphorylation and glucose production [11,64].…”
Section: Discussionmentioning
confidence: 99%
“…This dependency of the scaling approaches and their performance are widely discussed (27,(44)(45)(46). Recently, Lin et al (47) reported that HepatoPac® showed a better overall performance in predicting 73% of the drug clearances within twofold when applying conventional scaling for low-to very low-clearance compounds (≤1 mL min −1 kg −1…”
Section: Ivive Of In Vitro Clearance Assessmentsmentioning
confidence: 99%
“…Indeed, micropatterned co-cultures (MPCCs) of PHHs and 3T3-J2 murine embryonic fibroblasts can maintain prototypical hepatic morphology, secrete albumin and urea, and display high levels of CYP450 activities for 4–6 weeks2123. In this model, PHHs are first organized onto collagen-coated circular domains of empirically optimized dimensions in 24- or 96-well plates using semiconductor-driven soft-lithographic tools and then surrounded by 3T3-J2 fibroblasts.…”
mentioning
confidence: 99%